Use of a newly isolated yeast in the expression of recombinant proteins - Salleh, Abu Bakar; Oslan, Siti Nurbaya; Raja Abdul Rahman, Raja Noor Zaliha; Leow, Adam Thean Chor; Basri, Mahiran (2012)
The present invention relates to the use of a novel yeast strain isolated from a spoiled orange in Malaysia. The yeast strain of the present invention is used for the fast and high-yield expression of recombinant proteins. In preferred embodiments the proteins are expressed in the novel yeast strain under the control of methylotrophic promoters. The invention furthermore provides the novel yeast host cells comprising expression vector for the expression of bacterial lipases.